Visual Performance of Fermented Whey with the Addition of Pectin and Chitosan During 24 Hours Storage at Refrigerator Temperature - Ahmad Ni'matullah Al-Baarri; Sri Mulyani; Setya Budi Muhammad Abduh; Mulyana Hadipernata; Rafli Zulfa Kamil; Azka Nadiya Dzakiyalizz; Ghina Ulayya; Shabrina Nur Shaliha; Tri Yuliana; Ailsa Afra Mawarid; Widia Pangestika (Diponegoro University, 2023)
Fermentation of whey often faces problems with the product clarity due to the milk solids residue from previous cheese making process. The aim of this research was to determine the clarity and the performance of fermented whey precipitation process in the presence of pectin and chitosan as coagulant. Whey was initially pasteurized and added with pectin and chitosan prior to fermentation with mixed starter culture. Fermented whey was stored in refrigerator for 24 hours. Data were obtained using visual analysis by 15 semi-trained panelists. Qualitative scorings were given by (+) or (-) markings from the specified criteria. The data were compiled in a table, showcasing the observed characteristics at the initial and final states of fermentation. The results showed that the highest clarity (+++) was achieved by the fermented whey with the addition of pectin, as well as most stable sediment performance (+++) was also produced by pectin treatment. However, while fermented whey with the addition of pectin exhibited clarity, the level of clarity achieved by fermented whey with the addition of chitosan was superior.